CT dose equilibration and energy absorption in polyethylene cylinders with diameters from 6 to 55 cm - Li, Xinhua; Zhang, Da; Liu, Bob (Medical physics (Lancaster), 2015)
Purpose: ICRU Report No. 87 Committee and AAPM Task Group 200 designed a three‐sectional polyethylene phantom of 30 cm in diameter and 60 cm in length for evaluating the midpoint dose DL(0) and its rise‐to‐the‐equilibrium curve H(L) = DL(0)/Deq from computed tomography (CT) scanning, where Deq is the equilibrium dose. To aid the use of the phantom in radiation dose assessment and to gain an understanding of dose equilibration and energy absorption in polyethylene, the authors evaluated the short (20 cm) to long (60 cm) phantom dose ratio with a polyethylene diameter of 30 cm, assessed H(L) in polyethylene cylinders of 6–55 cm in diameters, and examined energy absorption in these cylinders. Methods: A geant4‐based Monte Carlo program was used to simulate the single axial scans of polyethylene cylinders (diameters 6–55 cm and length 90 cm, as well as diameter 30 cm and lengths 20 and 60 cm) on a clinical CT scanner (Somatom Definition dual source CT, Siemens Healthcare). Axial dose distributions were computed on the phantom central and peripheral axes. An average dose over the central 23 or 100 mm region was evaluated for modeling dose measurement using a 0.6 cm3 thimble chamber or a 10 cm long pencil ion chamber, respectively. The short (20 cm) to long (90 cm) phantom dose ratios were calculated for the 30 cm diameter polyethylene phantoms scanned at four tube voltages (80–140 kV) and a range of beam apertures (1–25 cm). H(L) was evaluated using the dose integrals computed with the 90 cm long phantoms. The resultant H(L) data were subsequently used to compute the fraction of the total energy absorbed inside or outside the scan range (Ein/E or Eout/E) on the phantom central and peripheral axes, where E = LDeq was the total energy absorbed along the z axis. Results: The midpoint dose in the 60 cm long polyethylene phantom was equal to that in the 90 cm long polyethylene phantom. The short‐to‐long phantom dose ratios changed with beam aperture and phantom axis but were insensitive to tube voltage. H(L) was insensitive to tube voltage and CT scanner model. As phantom diameter increased from 6 to 55 cm, Ein/E generally decreased but asymptotically approached constant levels on the peripheral axes of large phantoms. The curve of Ein/E versus scan length was almost identical to that of H(L). Similarly, Eout/E increased with scan length and asymptotically approached the equilibrium for large scan lengths. Eout/Deq was much less than the equilibrium length Leq where H(L) = 0.98, even with scan lengths much larger than Leq. Conclusions: The polyethylene phantom designed by ICRU Report No. 87 Committee and AAPM Task Group 200 is adequately long for assessing the midpoint dose and its equilibration in CT scanning. The short‐to‐long phantom dose ratios and the H(L) data provided in this paper allow easy evaluations of the midpoint dose, longitudinal dose distribution, and energy absorption in polyethylene phantoms. The results of dose equilibration and energy absorption presented herein may be insightful for the clinical CT scans with various subject sizes and scan lengths.